The Current Situations of Implementation in the Postgraduate Education Administration System at the National University of Laos - Bounnam Xomvimane; Bouadam Sengkhamkhoutlavong; Somsanith Vongkhamchanh (Journal of General Education and Humanities, 2026)
Postgraduate education administration at the National University of Laos has been a growing concern due to its improper management. This study, therefore, examines the current implementation of the administrative system using a quantitative approach. The data were collected from the target group of all 136 administrators and academic staff involved in postgraduate education administration. Descriptive statistics were used to analyze quantitative data. The document synthesis identified four key dimensions of the postgraduate administration system - curriculum management, teaching and learning management, student affairs, and academic title management. Each dimension was structured around input, process, output, and feedback components. The findings revealed that respondents rated all dimensions highly, indicating that the system is generally effective. However, significant challenges were identified across all components. These included limited budgets, shortages of specialized and qualified staff, and outdated facilities (input); complex and time-consuming procedures and insufficient needs assessments (process); delays in academic progress and curricula misaligned with current demands (output); and weak stakeholder collaboration and slow responsiveness to change (feedback). Overall, this study contributes academically by offering a systematic framework for postgraduate education administration and, practically, by providing evidence-based guidance to improve administrative effectiveness at the National University of Laos.